110k views
4 votes
What is the sum? (3/x2-9) + (5/x+3)

User Phse
by
5.2k points

2 Answers

4 votes
It’s (3/x2-9)+(5/x+3) go help me on my question!
User Hasan Abdullah
by
5.2k points
2 votes

Answer:

5x-12 / (x+3)(x-3)

Explanation:

Given expression:\frac{3}{x^2-9}+\frac{5}{x+3}

Using identity a^2-b^2=(a+b)(a-b), we get

=\frac{3}{(x+3)(x-3)}+\frac{5}{x+3}

Taking L.C.M. of the denominator, we get

\frac{3+5(x-3)}{(x+3)(x-3)}=\frac{3+5x-15}{(x+3)(x-3)}

=\frac{5x-12}{(x+3)(x-3)}

\Rightarrow\frac{3}{x^2-9}+\frac{5}{x+3}=\frac{5x-12}{(x+3)(x-3)}

User JMSilla
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.